1990
DOI: 10.1002/aic.690360610
|View full text |Cite
|
Sign up to set email alerts
|

Computation of flow patterns in circulating fluidized beds

Abstract: Flow regimes of dense‐phase vertical pneumatic transport of solids, referred to in the literature as circulating fluidized beds, have been computed using a generalization of the Navier‐Stokes equations for two fluids. In the less dense regime corresponding to volume fractions of solids of about 1%, the flow consists of centrally upward moving solids and downward moving clusters. The computations agree with observations made by high‐speed motion pictures and with measurements of radial solids concentrations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
129
0
12

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(150 citation statements)
references
References 25 publications
(22 reference statements)
9
129
0
12
Order By: Relevance
“…A transient two-dimensional approach simulates the dynamic behavior of a multiphase flow in a Circulating Fluidized Bed (CFB) within a reasonable period of time [23] [18]. It is noteworthy to mention that the value of 77 μm for the monosize distribution corresponds to the probabilistic mean diameter of the log-normal distribution to ensure a test-similarity.…”
Section: Resultsmentioning
confidence: 99%
“…A transient two-dimensional approach simulates the dynamic behavior of a multiphase flow in a Circulating Fluidized Bed (CFB) within a reasonable period of time [23] [18]. It is noteworthy to mention that the value of 77 μm for the monosize distribution corresponds to the probabilistic mean diameter of the log-normal distribution to ensure a test-similarity.…”
Section: Resultsmentioning
confidence: 99%
“…They can also be thought of as a natural consequence of the averaging processes involved in representing a discrete system of particles as a continuum (see, for instance, Drew [11], and Drew and Segal [12]). The particle-phase viscous effects have been investigated by many previous investigators (see, Tsuo and Gidaspow [13] and Gadiraju et al, [ 14]. Also, the particles are assumed to be dragged along by the fluid and, therefore, have no analog of pressure.…”
Section: Governing Equationsmentioning
confidence: 99%
“…Several studies reported in the literature have applied the above procedures. The traditional procedure was applied, for instance, by Tsuo and Gidaspow (1990), Sun and Gidaspow (1999), Huilin and Gidaspow (2003), and Cabezas- Gómez and Milioli (2003, 2005a, among others. The procedure based on the algebraic version of the KTGF was applied, for instance, by Syamlal et al (1993), Boemer et al (1995), van Wachem et al (1998), and Guenther and Syamlal (2001), among others.…”
Section: Introductionmentioning
confidence: 99%